Prospective multicentre evaluation of a novel, low-profile transapical delivery system for self-expandable transcatheter aortic valve implantation: 6-month outcomes. (14th March 2018) - Conradi, Lenard; Hilker, Michael; Kempfert, Jörg; Börgermann, Jochen; Treede, Hendrik; Holzhey, David M; Schröfel, Holger; Kim, Won-Keun; Schaefer, Ulrich; Walther, Thomas
Abstract: OBJECTIVES: We assessed the safety and efficacy of a novel low-profile, 22-Fr transapical delivery system together with the ACURATE neo ™ resheathable transcatheter heart valve. METHODS: This prospective, single-arm, multicentre study enrolled 60 patients with severe symptomatic aortic stenosis and high surgical risk ineligible for transfemoral access. Primary end points were 6-month mortality and procedural success. RESULTS: The mean age of patients was 79.8 ± 4.7 years, and the patients had severe comorbidities including coronary artery disease (71.7%), diabetes (38.3%), atrial fibrillation (30.0%) and chronic obstructive pulmonary disease (21.7%); logistic EuroSCORE-I, -II and the Society of Thoracic Surgeons (STS) scores were 20.9 ± 8.9%, 6.1 ± 5.0% and 4.3 ± 2.9%, respectively. A non-rib spreading approach using soft tissue retractors only was used in 88.3% of patients ( n = 53). Resheathing and repositioning of transcatheter heart valve were performed in 6.7% of cases ( n = 4); the device implantation time was 3 ± 2 min. Apical access site complications occurred in 1.7% ( n = 1). Procedural success was 98.3% ( n = 59), and procedural success in the absence of major adverse cardiac and cerebrovascular events at 30 days was 90.0% ( n = 54). At 30 days, cardiovascular and overall mortality were 8.3% ( n = 5), stroke rate was 1.7% ( n = 1), and 17.2% of patients ( n = 10) received a permanent pacemaker implant. No paravalvular leakage ≥2+ was observed, and the mean transvalvular gradient was 5.9 ± 2.7 mmHg. At 6 months, survival was 84.3% with sustained haemodynamic results. CONCLUSIONS: This study indicates safety and efficacy of transapical aortic valve implantation using a novel low-profile delivery system. High procedural success, short implantation times and a low rate of apical access site complications underline the favourable safety profile and ease of use. Clinical trial registration: ClinicalTrials.gov: NCT02950428.